2016
DOI: 10.2147/tcrm.s97024
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with postoperative pain after ophthalmic surgery: a prospective study

Abstract: BackgroundRisk factors associated with postoperative pain intensity and duration, as well as consumption of analgesics after ophthalmic surgery are poorly understood.MethodsA prospective study was conducted among adults (N=226) who underwent eye surgery at the University Hospital Split, Croatia. A day before the surgery, the patients filled out questionnaires assessing personality, anxiety, pain catastrophizing, sociodemographics and were given details about the procedure, anesthesia, and analgesia for each po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…We suspected that age might have affected the pain during surgery. It has been shown that aging may impact pain perception and expression (Omar et al, 2012;Tighe et al, 2015;Lesin et al, 2016). Unpleasant and severe ocular irritation symptoms may not be reported as pain related to the surgery by elderly patients, as observed in the present study.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We suspected that age might have affected the pain during surgery. It has been shown that aging may impact pain perception and expression (Omar et al, 2012;Tighe et al, 2015;Lesin et al, 2016). Unpleasant and severe ocular irritation symptoms may not be reported as pain related to the surgery by elderly patients, as observed in the present study.…”
Section: Discussionsupporting
confidence: 66%
“…Some authors tried to determine factors affecting patients' pain intensity during "in office" intravitreal injection procedure but did not observe correlation between ophthalmological diagnosis and pain intensity (Rifkin and Schaal, 2012). Similar outcomes were found for other ophthalmic surgical procedures (Lesin et al, 2016). The association of postoperative complications with pain intensity has not been examined yet.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding level of education the current study found insignificant correlation with postoperative pain and this finding is consistent with the qualitative systemic review study conducted to determine the predictors of postoperative pain and analgesics consumption (Vivian et al, 2009). Another study conducted in Croatia by (Lesin et al, 2016) stated insignificant correlation between level of education and postoperative anxiety. The present study showed significant correlation between level of education and preoperative anxiety.…”
Section: Discussionmentioning
confidence: 93%
“…The same authors added that postoperative pain level was higher in younger patients than older and this is incongruent with our finding. Another study conducted in Croatia by (Lesin et al, 2016) reported that age and preoperative anxiety are significantly associated with postoperative pain. Recent study conducted in Canada by (Yang et al,2019) to identify preoperative predictors of poor postoperative pain control in adults undergoing inpatient surgery highlighted that younger age is significantly associated with postoperative pain which is inconsistent with the current study finding.…”
Section: Discussionmentioning
confidence: 98%
“… 1 , 2 Studies indicate that 75% surgical patients experience postoperative pain, with approximately 30% enduring moderate to severe discomfort. 3 Pain can give rise to a range of complications, adversely impacting respiratory, circulatory, endocrine, and other somatic functions, as well as psychological well-being. It is widely acknowledged as the fifth most critical vital sign in human healthcare.…”
Section: Introductionmentioning
confidence: 99%